PENERAPAN PROBLEM BASED LEARNING PADA MATERI STATISTIKA DI KELAS XI SMA NEGERI 1 SUNGAI RAYA - Pratama, Rendy; Jamiah, Yulis; T, Ahmad Yani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to find out whether the application of  Problem based learning was effective in teaching a statistics materials to the eleventh grade students of SMA Negeri 1 Sungai Raya. This research is classified as a pre-experimental and conducted in form of one case study or post-test only design. The population of this research were 162 students of eleventh grade, and the samples were 40 students. Purposive sampling was used to choose the sample. The result of the data analysis showed that the study result was not reached, learning activity was quite active and student gave a positive respons. Based on the research findings, it can be concluded that the application of  Problem based learning was  effective in teaching a statistic materials  to the grade XI 2 students of SMA Negeri 1 Sungai Raya because the study result was reached and learning activity was quite active.Keyword: Problem Based Learning, Response, Student Activities